Studi In Silico Potensi Antikanker Senyawa Kaempferida - Arif Fadlan; Tri Warsito; Sarmoko Sarmoko (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2022)
Active compounds as therapeutic agents are mainly found in natural products. Kaempferia pandurata from Kaempferia Genus has been used for the treatment of diseases. K. pandurata contains kaempferol (KMP) which exhibits various biological activities such as anticancer. KMP correlates to death-associated protein kinase 1 (DAPK1) relates to tumor suppression and apoptotic and autophagy mediation. This research aims to evaluate the anticancer potential of kaempferide (a methylated KMP at the C4’ position) against DAPK1 in silico. The research was performed through molecular docking to DAPK1 (5AUX and 5AV3), anticancer activity prediction, drug-likeness analysis, and ADMET (absorption, distribution, metabolism, excretion, and toxicology) evaluation. The binding affinity of kaempferide was -8.0 kcal/mol for 5AUX and 5AV3, respectively. The highest anticancer activity of kaempferide was shown against the prostate carcinoma cell line CWR22R. Kaempferide showed no violation to Lipinski-Veber rule and had good ADMET profile. Keywords: in silico, anticancer, kaempferide Senyawa aktif dengan potensi terapeutik banyak ditemukan dalam bahan alam. Kaempferia pandurata dari genus Kaempferia telah digunakan dalam pengobatan berbagai penyakit. K. pandurata mengandung kaempferol (KMP) dengan aktivitas biologis beragam, salah satunya adalah antikanker. KMP juga dapat berikatan dengan death-associated protein kinase 1 (DAPK1) yang berhubungan dengan penekanan tumor dan mediasi apoptosis dan autofagi. Penelitian ini mempelajari potensi antikanker kaempferida (KMP yang termetilasi pada posisi C4’) terhadap DAPK1 secara in silico. Penelitian dilakukan melalui penambatan molekular terhadap DAPK1 (5AUX dan 5AV3), perkiraan aktivitas antikanker, analisis drug-likeness, dan prediksi ADMET (absorption, distribution, metabolism, excretion, and toxicology). Afinitas ikatan kaempferida masing-masing sebesar -8,0 kkal/mol untuk 5AUX dan 5AV3. Aktivitas antikanker tertinggi kaempferida ditunjukkan terhadap cell line karsinoma prostat CWR22R. Kaempferida tidak melanggar aturan Lipinski-Veber sesuai analisis drug-likeness dan memiliki profil ADMET yang cukup baik. Kata kunci: in silico, antikanker, kaempferida